The lowest Landau level in QCD - Bruckmann Falk; Endrődi Gergely; Giordano Matteo; Katz Sándor D.; Kovács Tamás G.; Pittler Ferenc; Wellnhofer Jacob (EPJ Web of Conferences, 2017)
The thermodynamics of Quantum Chromodynamics (QCD) in external (electro-)magnetic fields shows some unexpected features like inverse magnetic catalysis, which have been revealed mainly through lattice studies. Many effective descriptions, on the other hand, use Landau levels or approximate the system by just the lowest Landau level (LLL). Analyzing lattice configurations we ask whether such a picture is justified. We find the LLL to be separated from the rest by a spectral gap in the two-dimensional Dirac operator and analyze the corresponding LLL signature in four dimensions. We determine to what extent the quark condensate is LLL dominated at strong magnetic fields.